PENGARUH NILAI SOSIAL, PENGHARGAAN FINANSIAL DAN PERTIMBANGAN PASAR KERJA TERHADAP MINAT MAHASISWA DALAM PEMILIHAN KARIER SEBAGAI AUDITOR - Meliawati; Prima, Argo Putra (SCIENTIA JOURNAL, 2024)
ABSTRACT The rapid development of globalization and technology has significantly impacted the business world, triggering progress and growth. Career choices for students, especially as auditors, have a significant impact on their personal future and also on the industrial growth in Batam City. This research aims to explore the relationship between social values, financial rewards, and labor market considerations on students' interest in choosing a career as an auditor. This research utilizes a quantitative research method. The results show that social values and financial rewards have a positive and significant influence on students' interest in choosing a career as an auditor, while the labor market consideration variable has a negative and insignificant effect on students' interest in choosing a career as an auditor. This study is expected to provide a more comprehensive understanding of the shortage of auditors in Batam. Keywords: Social Value, Financial Reward, Job Market Considerations and Interests.